PD-L1 and CD8+ T cell evaluation in breast cancers and their correlation with clinicopathological parameters - Kazmi, Sayher; Shawana, Sumayyah; Jamal, Nighat (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the immunohistochemical expression of Programmed cell Death Ligand 1 and intratumoural cluster of differentiation-8-positive T lymphocyte count in primary breast cancer cases, and to ascertain their association with different clinicopathological parameters. Method: The cross-sectional study was conducted at the Pakistan Navy Station Shifa Hospital, Karachi, from January 2020 to December 2021, and comprised patients of breast cancer regardless of age. Representative tissue blocks, both prospective and from the 2019 institutional archives, were exposed to immunohistochemical staining with Programmed cell Death Ligand 1 and intratumoural cluster of differentiation-8-positive T lymphocyte antibodies. Pathological and clinical records were used for assessing clinicopathological parameters. Data was analysed using SPSS 23. Results: Of the 70 women with mean age 52.04±12.54 years, 30(42.9%) expressed high Programmed cell Death Ligand 1 positivity, and 55(78.6%) revealed low intratumoural cluster of differentiation-8-positive T lymphocyte count, while 23 (32.9%), had both Programmed cell Death Ligand 1 high positivity and low intratumoural cluster of differentiation-8-positive T lymphocyte count. The association between Programmed cell Death Ligand 1 and intratumoural cluster of differentiation-8-positive T lymphocytes was not significant (p=0.813). A strong significant association was observed between Programmed cell Death Ligand 1 expression and progesterone receptor negative status (p=0.008). No significant association was observed with any other clinicopathological parameter. Conclusion: Programmed cell Death Ligand 1 high positivity and low intratumoural cluster of differentiation-8-positive T lymphocyte count were together observed in one-third of the breast cancer cases. A strong significant association existed between Programmed cell Death Ligand 1 high positivity and progesterone receptor negative status. Key Words: Breast cancer, Programmed cell death 1 ligand 1 protein human, CD8 positive T lymphocytes, Immunohistochemistry.